2014
DOI: 10.1007/s00464-014-3908-9
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic approach is associated with increased incidence of atrial fibrillation after esophageal resection

Abstract: Transthoracic approach is an independent risk factor for the development of new-onset AF after esophagectomy. New-onset AF is associated with severe post-operative complications and longer hospital stay. Minimally invasive approach does not decrease the incidence of new-onset AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 20 publications
3
53
0
Order By: Relevance
“…In the present study, the incidence of postoesophagectomy AF in the placebo group was 30 per cent, similar to previous reports. Mechanisms of AF after oesophagectomy remain unclear, although it may be partially explained by surgical trauma to the cardiac fibres of the sympathetic and parasympathetic nerves.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In the present study, the incidence of postoesophagectomy AF in the placebo group was 30 per cent, similar to previous reports. Mechanisms of AF after oesophagectomy remain unclear, although it may be partially explained by surgical trauma to the cardiac fibres of the sympathetic and parasympathetic nerves.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have shown that postoperative AF is associated with other severe complications such as anastomotic leaks and pulmonary complications after oesophagectomy. Whether a leak contributes to the onset of AF or the haemodynamic consequences of AF increase the likelihood of a leak is a subject of debate, and one of the aims of the present study was to see whether the prevention of new‐onset AF would lead to a reduction in other postoperative complications.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Following a lung lobectomy, atrial KCNE1 (potassium channel subunit) down-regulation was identified, which suggested an increased outward current in atrial myocytes, shortened atrial action potentials, and enhanced susceptibility to POAF [50]. Furthermore, a strong relationship was observed between postoperative hypoxia and AF after surgery for esophageal carcinoma [51]. Ma et al hypothesized that factors predisposing one to postoperative hypoxia (like COPD) could play a role in the development of AF [49].…”
Section: Acute Factors Facilitating Poaf In Cancer Therapymentioning
confidence: 99%